Editorial : Newborn survival : changing the trajectory over the next decade - Darmstadt, G.L. (2012)
Introduces the series of articles presenting a comprehensive analysis of the changes in newborn care and survival over the last decade at global level, as well as five detailed country assessments undertaken by over 60 experts from government and multiple organisations, in order to better understand the process of taking solutions to scale and how to accelerate progress towards reductions in mortality and morbidity.